Studi Struktur Kristal Film Tipis Galliumantimony yang Ditumbuhkan dengan MOCVD Reaktor Vertikal - Zulirfan Zulirfan; Euis Sustini; Maman Budiman (Indonesian Journal of Physics, 2001)
GaSb thin films have been grown by using vertical reactor MOCVD on (100) SI-GaAs substrates. TMGa and TDMASb were used as a precursor of group III and V respectively, with H2 as gas carrier. Films were grown at the growth temperatures 5200C and 540 oC as a function of V/III ratio. The range of V/III ratio were 0,4 - 3,1. The ex-situ characterization, XRD and SEM were used to examine the crystal structure and the morphology of the films, respectively. EDS characterization were used to find the composition of Ga and Sb atoms in the films. The increased of V/III ratio were found to have a significant effect on the both properties. Film grown at the lowest V/III ratio (0,4) shows a polycrystal structure with several peaks of GaSb crystal’s orientation, and bad surface morphology. Films grown at V/III ratio ranged about 1.0 to 3.1 show the same crystal’s orientation of GaSb, of (200) and (400). The better surface morphology were found at the growth temperature 540 oC with V/III ratio 2,0.